Pengaruh Harga, Kualitas Produk, dan Influencer Review Terhadap Keputusan Pembelian Produk Skincare Glad2Glow - Esteur Novia Susantika; Januar Wibowo; Antok Supriyanto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The continuous growth of Indonesia's skincare industry has intensified market competition, encouraging companies to better understand the factors that influence consumers' purchasing decisions. This study aims to investigate the effects of price, product quality, and influencer reviews on the purchase decisions of Glad2Glow skincare products among followers of the @glad2glow Instagram account. A quantitative research approach was employed using a survey method, with questionnaires distributed to 190 respondents who follow the @glad2glow Instagram account and have previously used Glad2Glow products. The respondents were selected through purposive sampling, and the data were analyzed using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) approach with SmartPLS 4 software. The results reveal that price, product quality, and influencer reviews each have a positive and significant influence on consumers' purchase decisions. Among these variables, price exerts the strongest effect, while product quality and influencer reviews also make significant contributions to consumers' purchasing decisions. Furthermore, the coefficient of determination (R²) of 0.539 indicates that these variables collectively explain 53.9% of the variation in purchase decisions, whereas the remaining 46.1% is attributed to other variables beyond the scope of this study. These findings imply that maintaining competitive pricing, ensuring product quality, and utilizing credible influencer reviews are essential strategies for improving consumers' purchase decisions toward Glad2Glow skincare products.